Você unidade de medida: sobre escrever percursos que o corpo aponta como direção - Souza, Bianca Ziegler de (2017)
This text is a result of the research developed in the Academic Master in Arts of the Graduate Program in Arts of the Federal University of Ceará, specifically in the context of the discussions provided by the Laboratory of Research in Body, Communication and Art - LICCA and accompanies the development of the artistic project You, unit of measure that resulted in six artistic propositions. The research starts from the concept of self-writing, approached by Foucault, to develop a methodology that is based on the process of writing and appropriating fragments of texts - reports, memoirs, notes in notebooks, calendars and loose papers, letters and emails received and envoys - who both guide and design the paths of thought and the creation of artistic propositions in video, photography, performative action, participatory action and publication. The works and the texts are built on the idea of the body as a unit of measure in the world and territory of exploration and tangentiate the thought about body and space, the encounter, the passion, the look, the writing, the language and also the actions that suggest the verb to publish.